Enhancing Student Learning Motivation through Private Tutoring: An Analysis of Teaching Skills - Pratiwi, Wiwin Anggita; Eka Tuti Zurika; Nadiya Shofiyah (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2023)
Purpose – The primary objective of this study was to analyze the influence of teaching skills in private tutoring on student learning motivation. Design/methods– The research adopted a quantitative approach, utilizing a descriptive correlational analysis method to understand the interaction between private tutoring teaching skills (independent variable) and student learning motivation (dependent variable). The sample consisted of 63 sixth-semester students from the Faculty of Tarbiyah and Teacher Training engaged in private tutoring. Data were collected through questionnaires and analyzed using SPSS and SmartPLS 4, focusing on validity, reliability, and hypothesis testing. Findings – The study revealed significant correlations between teaching skills in private tutoring and various motivational factors, including intrinsic and extrinsic motivation, relevance, and knowledge transfer. It demonstrated the substantial influence of private tutor teaching skills on enhancing student learning motivation. Research implications/limitations – This research contributes to the broader understanding of the role of teaching skills in student motivation, particularly in private tutoring contexts. However, the study acknowledges its limitations, including its sample size and focus, suggesting the need for further research with a more diverse sample and exploration of additional motivational factors. Practical implications – The findings have practical implications for teacher training programs, highlighting the necessity of developing personalized teaching strategies to foster student engagement and learning outcomes. The study suggests that private tutors with specific pedagogical competencies can significantly impact student motivation compared to regular classroom teaching. Originality/value – This research offers new insights into educational psychology by demonstrating the significant impact of private tutoring teaching skills on student learning motivation. It fills a gap in the existing literature by providing quantitative evidence of this relationship and suggesting practical applications in teacher training and educational practice.